(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Making decisions is considered as the key role in achieving the desired goals within any organization. Moreover, making decisions in oil & gas industry is becoming a key factor for improving the work performance throughout practicing the most effective tools and techniques. The main purpose of this paper is to identify how individuals making their decisions within operating oil and gas companies. The required data for this paper were acquired by conducting several interviews with decision makers, and a questionnaire survey was also developed, besides reviewing the related literatures. Decision making processes in Libyan oil & gas operating companies were being investigated. The main findings show that over half of participants always consider safety, security and uncertainty issues when making their decisions, meaning that, it is a good indication of taking precautions when making decisions. Additionally, the majority of participants always double check their information resources, which is also a good indication of increasing the quality decisions and enhancing the work performance. Based on the findings, a number of recommendations were proposed for improving the processes of making proper and effective decisions within this business area